Between tinkering and transformation: A contemporary appraisal of climate change adaptation research on the world's islands - Petzold, Jan; Joe, Elphin T.; Kelman, Ilan; Magnan, Alexandre K.; Mirbach, Charlotta; Nagle Alverio, Gabriela; Nunn, Patrick D.; Ratter, Beate M. W.; , The Global Adaptation Mapping Initiative Team (Frontiers in Climate, 2023)
Islands are at the centre of discourses on climate change. Yet despite extensive work on diverse island systems in a changing climate, we still lack an understanding of climate change-related responses amongst islands and what shifting from what might be called ‘tinkering’ (perhaps heat warnings) to ‘transformational’ adaptation (perhaps relocation) means for these vastly different landmasses which are often grouped together by default. Through a systematic review of the climate change adaptation scientific literature, this paper critically reflects on how considering islands as a homogenous ensemble and the use of buzzwords such as ‘transformational adaptation’ may be problematic for diverse island realities under climate change. Our findings show that the adaptation evidence base actually provides literature on contrasting island types and cultural and political contexts, including Small Island Developing States as well as other island territories. This study finds research gaps with respect to regions (e.g., South America, Africa, Mediterranean) and that there is overall both little evidence of and a lack of context-specific definitions of transformational adaptation in island contexts. The adaptation literature does not yet fully reflect the experiences or needs of islands regarding transitions and transformations throughout history.